Analisis Tradisi Mappanini Bosi Dalam Pernikahan Masyarakat Bugis Perspektif Urf’ - Ahsan, Muh; Suci Cahaya Ningsih; Dewi Nirwana; Sitti Faisyah Az Zahra Darwis; Nur Hazmi Asyikin (Muhammadiyah University of Surabaya, 2025)
This research explores the practice of Mappanini Bosi (rain diversion) in Bugis wedding ceremonies in Waetuoe Village, Lanrisang District, Pinrang Regency. The issue examined in this study concerns the persistence of this traditional practice and its relation to urf’. The purpose is to analyze how Mappanini Bosi is conducted, what meanings it holds for the community, and how it aligns with Islamic beliefs. The study employs a qualitative field research design using a phenomenological approach. Data were obtained through interviews with local sanro (traditional healers or rain shamans) and community members, supported by secondary sources such as books, journals, and previous research. The findings show that Mappanini Bosi is performed to ensure favorable weather during important ceremonies, using ritual tools such as rice, fish without broth, cigarettes, lighters, and seven kinds of cakes. Although it involves traditional spells and rituals, practitioners emphasize that success ultimately depends on the will of Allah SWT. The study concludes that this tradition reflects local cultural values and spiritual beliefs without contradicting Islamic teachings, as long as it remains rooted in faith in God’s power. However, its continuity may face challenges from modernization and scientific reasoning. Keywords: Mappanini Bosi, Bugis Marriage Tradition, ‘Urf.